Esboço de uma Inquirição Filosófica Pragmático-Expressivista da Linguagem sobre as ‘Investigações Filosóficas’ - Marra Rodrigues, Osvaldino (Nómadas. Critical Journal of Social and Juridical Science, 2010)
The central thesis of Modern Philosophy assumes a rational conception of the mind. It means to say that a rational agent has, potentially, the conditions necessary to know. In this direction, theory and practice concepts appear as disconnected. More specifically, the concepts of Modern Philosophy, both Cartesian and Lockean heritage, focus on theory over practice. Thus, the modern anthropology has established a hypothesis supported by theoretical and epistemological subject ideally disengaged, because the intelligibility conditions would be properties of individualized minds of agents, permeated by the adoption of a theory, or at least an assumption, about how things works. Against this prevailing conception, Wittgenstein, in Philosophical Investigations, argued to the contrary: the forms of life practices and language games are what sustains and makes possible a theory, not the inverse. To develop this argument, we have support on two contemporary authors, Richard Rorty and Charles Taylor.